1999
DOI: 10.1086/301128
|View full text |Cite
|
Sign up to set email alerts
|

The Extraordinary “Superthin” Spiral Galaxy UGC 7321. I. Disk Color Gradients and Global Properties from Multiwavelength Observations

Abstract: We present B-and R-band optical imaging and photometry, Hα narrow-band imaging, near-infrared H-band imaging, and H i 21-cm spectroscopy of the nearby (V h =407 km/s), Sd spiral galaxy UGC 7321. UGC 7321 exhibits a remarkably thin stellar disk with no discernible bulge component. The galaxy has a very diffuse, low surface brightness disk, which appears to suffer relatively little internal extinction in spite of its nearly edge-on geometry (i ≈88 • ). If seen face-on, UGC 7321 would have an observed central B-b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(120 citation statements)
references
References 58 publications
(97 reference statements)
6
113
1
Order By: Relevance
“…Observations by Matthews et al (1999) that found a significant fraction of young stars support our results. Detailed studies of the vertical disk structure indicate multiple disk components (Matthews 2000).…”
Section: Rotation Curve Decompositionsupporting
confidence: 90%
See 2 more Smart Citations
“…Observations by Matthews et al (1999) that found a significant fraction of young stars support our results. Detailed studies of the vertical disk structure indicate multiple disk components (Matthews 2000).…”
Section: Rotation Curve Decompositionsupporting
confidence: 90%
“…We found the projected central R-band surface brightness to be 22.0 mag arcsec −2 , with a scalelength of 4.0 ± 0.3 kpc, in agreement with that measured by Pohlen et al (2003). The projected central surface brightness is consistent with the B and R-band measurement by Matthews et al (1999) when the internal extinction model that Matthews et al used is factored in. The projected surface brightness shows a small nuclear feature smaller than 1 kpc, and an exponential profile from 0.5 to 6.5 kpc, declining steeply after 7 kpc.…”
Section: Stellar Surface Brightness and Deprojected Luminosity Densitsupporting
confidence: 87%
See 1 more Smart Citation
“…However, even then, the amount of reddening due to dust will be insufficient to explain the large radial color gradients now observed in a number of LSB galaxies (de Blok, van der Hulst, & Bothun 1995 ;MGvD99 ;Matthews et al 2000 ;Bell et al 2000). Thus some LSB galaxies must have large intrinsic stellar population and/or metallicity gradients in their disks.…”
Section: Discussionmentioning
confidence: 99%
“…Other explanations for localised regions of increased thickness are infalling material from a companion or disruption by a companion, however UGC 7321 is an isolated galaxy. The high symmetry of the flaring on both sides of the centre, and the high stellar disk major-to-minor axis ratio (a/b = 10.3 at μ R = 25.0 mag arcsec −2 , Matthews et al 1999) render disruption by an undetected neighbouring galaxy rather implausible. 3 We thank Lia Athanassoula for pointing this out.…”
Section: Ugc 7321mentioning
confidence: 99%